Differential Healing Patterns of Mucosal Seal on Zirconia and Titanium Implant - Lee, Dong-Joon; Ryu, Joon-Sang; Shimono, Masaki; Lee, Keun-Woo; Lee, Jong-Min; Jung, Han-Sung (Frontiers in Physiology, 2019)
Zirconia implants have become an alternative to titanium implants due to several advantages. The zirconia implant is relatively esthetic and highly resistant to bacteria. While biomaterial studies for zirconia implants have considerably accumulated, in vivo studies have not yet progressed. The aims of the present study were (1) to determine the characteristics of periodontal cells on zirconia and titanium, (2) to investigate the difference in mucosal seals between zirconia and other implants and (3) to provide evidence for determining which material is more advantageous for clinical use. In the present study, small implant fixtures that can be applied to the jawbone of mice were manufactured. The periodontal cells proliferated best on zirconia surfaces. In addition, the evidence suggests a stronger mucosal seal and more adequate prevention of peri-implant epithelium migration in the zirconia implant when compared with other conventional materials. In conclusion, zirconia was favorable and advantageous in aspect of the mucosal seal.